2018
DOI: 10.1002/slct.201800779
|View full text |Cite
|
Sign up to set email alerts
|

C‐N and N‐N bond formation via Reductive Cyclization: Progress in Cadogan /Cadogan‐Sundberg Reactionǂ

Abstract: Cadogan/Cadogan‐Sundberg cyclization reaction has been reported as one of the most efficient routes for the synthesis of a wide variety of N‐heterocycles from the easily accessible starting materials such as o‐nitrobiaryls or o‐nitroarenes, o‐nitrostyrenes by treating with tetravalent phosphorus compounds (trialkyl or triaryl phosphines or trialkyl phosphites). The reaction has been successfully employed in Carbon‐Carbon as well as Carbon‐Nitrogen bond formation for the scaffolds like carbazole, indoles, couma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 90 publications
0
19
0
Order By: Relevance
“…Synthesis of S,N -heterotetracene H -SN4 13 and related derivatives by Cadogan reaction of nitro-substituted precursors . Another possibility for the preparation of fused pyrrole rings is established by the Cadogan reaction [ 40 ]. Well-known examples are the reductive cyclization of 2-nitro-1,1’-biphenyls with triethyl phosphite or phosphanes as reducing agent to provide carbazoles covering a wide substrate and functional group spectrum [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Synthesis of S,N -heterotetracene H -SN4 13 and related derivatives by Cadogan reaction of nitro-substituted precursors . Another possibility for the preparation of fused pyrrole rings is established by the Cadogan reaction [ 40 ]. Well-known examples are the reductive cyclization of 2-nitro-1,1’-biphenyls with triethyl phosphite or phosphanes as reducing agent to provide carbazoles covering a wide substrate and functional group spectrum [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Based on the mechanism research experiments and literature investigations, [14b,15,20] a possible mechanism for this electrochemical reductive arylation of arylboronic acids with nitroarenes is proposed in Scheme 6. Two possible mechanism paths are proposed.…”
Section: Methodsmentioning
confidence: 99%
“…313,314 Among the ergot alkaloids (EAs) family of naturally occurring compounds, lysergic acid 315 is the most broadly identied member and various semisynthetic derivatives have been clinically utilized for treating various neurological diseases. In 2015, Boger et al demonstrated 316 that the total synthesis of dihydrolysergic acid (363) and dihydrolysergol (364) relied on a palladium (0)-mediated intramolecular Larock indole cyclization for the formation of the tricyclic indole and also a consequently inverse electron demand Diels-Alder reaction. The total synthesis of dihydrolysergic acid (363) and dihydrolysergol (364) were commenced from 2-bromoaniline (359).…”
Section: Larock Indole Synthesismentioning
confidence: 99%
“…In 2015, Boger et al demonstrated 316 that the total synthesis of dihydrolysergic acid (363) and dihydrolysergol (364) relied on a palladium (0)-mediated intramolecular Larock indole cyclization for the formation of the tricyclic indole and also a consequently inverse electron demand Diels-Alder reaction. The total synthesis of dihydrolysergic acid (363) and dihydrolysergol (364) were commenced from 2-bromoaniline (359). The latter, aer ve steps, gave homopropargylic alcohol 360, that through an intramolecular palladium(0)-mediated Larock indole annulation gave the tricyclic indole 361.…”
Section: Larock Indole Synthesismentioning
confidence: 99%
See 1 more Smart Citation